2000
DOI: 10.1002/(sici)1097-4644(20000615)77:4<517::aid-jcb1>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of α5β1 integrin functions by the phospholipid and cholesterol contents of cell membranes

Abstract: Several modifications of the alpha5beta1 integrin, which alter its intracellular and extracellular interaction with fibronectin and other proteins, have been reported. However, the significance of the lateral mobility of integrin molecules in the plasma membrane, as a regulator of their distribution and function, is poorly understood. We examined this problem by increasing the cholesterol content of plasma membranes, and consequently modifying the fluidity of membrane phospholipids, in rat fibroblasts. Under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 0 publications
2
29
0
Order By: Relevance
“…Thus, IgV-GPI appeared to be superior to wild-type CD47 in its ability to confer protection against cyclodextrin-induced disruption of cell adhesion as a result of its increased enrichment in cyclodextrin-resistant membrane domains. A correlation between raft localization and integrin clustering has been previously reported in fibroblasts, where membrane cholesterol levels affected the clustering of ␣ 5 ␤ 1 (23), and in T-cells, where LFA-1-mediated cell binding was shown to be enhanced by clustering of membrane rafts via the GPI-anchored protein CD24 (24). In raft membranes, integrin-integrin contacts may be promoted by a more extreme hydrophobic environment, or by other physical properties such as membrane thickness (37).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Thus, IgV-GPI appeared to be superior to wild-type CD47 in its ability to confer protection against cyclodextrin-induced disruption of cell adhesion as a result of its increased enrichment in cyclodextrin-resistant membrane domains. A correlation between raft localization and integrin clustering has been previously reported in fibroblasts, where membrane cholesterol levels affected the clustering of ␣ 5 ␤ 1 (23), and in T-cells, where LFA-1-mediated cell binding was shown to be enhanced by clustering of membrane rafts via the GPI-anchored protein CD24 (24). In raft membranes, integrin-integrin contacts may be promoted by a more extreme hydrophobic environment, or by other physical properties such as membrane thickness (37).…”
Section: Discussionsupporting
confidence: 55%
“…Membrane cholesterol levels have been reported to affect the clustering of ␣ 5 ␤ 1 in rat fibroblasts (23), and in T-cells, via the GPI-anchored protein CD24 (24). Because we have shown that anti-LIBS binding is not significantly affected by cyclodextrin treatment (Fig.…”
Section: Binding Of Libs Antibodies To ␣ V ␤ 3 Is Enhanced By Cd47mentioning
confidence: 64%
See 1 more Smart Citation
“…b 1 -Integrin subunit is indeed expressed in many cell types including fibroblasts, the precursors of adipocytes. 30 We first looked for the presence of b 1 -integrin in isolated large and small adipocytes. Western blot analysis clearly shows that b 1 -integrin is detected in adipocytes; furthermore, there was a 60% increase in the concentration of b 1 -integrin in large compared to small cells (1.670.07, n ¼ 6 and 1.070.06, n ¼ 6, arbitrary units per cell, respectively, Po0.01).…”
Section: Resultsmentioning
confidence: 99%
“…This pathway is also regulated by the lipid composition of plasma membrane, and Gopalakrishna et al 30 have demonstrated in rat fibroblasts that an increase in membrane cholesterol diminishes ERKs activation through regulation of b 1 -integrin function. If such a mechanism exists in adipose cell, the decrease in membrane cholesterol content that we observed in large adipocytes 20 could be a signal for the modulation of b 1 -integrin activity and the subsequent activation of ERKs pathway.…”
Section: Discussionmentioning
confidence: 99%